Blended Approach to Occupational Performance (BAOP): Guidelines Enabling Children with Autism - Jordan M. Skowronski; Jack R. Engsberg (Scholarworks @ WMU, 2017)
The performance of daily activities is impacted by motor impairments in children with autism spectrum disorders (ASD). Research has recently demonstrated the prevalence and specificity of motor impairments in people with ASD. The motor learning of individuals with ASD is partially intact, and evidence suggests that a method to alter skill learning and repeated practice of motor sequences might be beneficial. Aiming to use this knowledge to guide occupational therapy interventions, initial guidelines for children with ASD blended Cognitive Orientation to daily Occupational Performance (CO-OP) with virtual reality (VR) were created. An expert panel reviewed the initial guidelines. The results from the semi-structured expert panel discussion were to (a) increase the number of sessions, (b) provide more visuals to children, and (c) use VR as a reinforcer. Guidelines were revised accordingly. The revised guidelines, called Blended Approach to Occupational Performance (BAOP), are ready for further testing.